Risk Factors of Agitation Among Schizophrenia Patients in Dr. Amino Gondohutomo Semarang Regional Psychiatric Hospital: A Cross-Sectional Study - Ratna sofa, Yulia; Noerhidajati, Elly; Woroasih, Sri; Intan Tri Hardini (Jurnal Psikiatri Surabaya, 2024)
Introduction: Schizophrenia is a severe mental disorder associated with deterioration in the functions of daily life and social functions because it can reduce a person’s quality of life. In the acute phase, many schizophrenic patients have agitated behavior where this behavior will risk injuring themselves and others because of that treatment costs increase. to determine the risk factors for agitation in schizophrenic patients in terms of age, gender, marital status, occupation, genetic history, and presence or absence of stressors. Methods: This research is a descriptive analytic using a cross-sectional design. The population in this study were schizophrenic patients at Dr. Amino Gondohutomo Semarang Regional Psychiatric Hospital. Research subjects will be taken using consecutive sampling techniques that meet the inclusion and exclusion criteria. Data collection used medical record data and the PANNS EC score to determine whether there was agitation. Data analysis included descriptive analysis with frequency and percentage distributions as well as hypothesis testing using the Chi Square test and logistic regression. Results: From the results of the Chi Square test and logistic regression, it was found that the factors of young age, male sex, unmarried, and unemployed were significant for PANSS EC with a prevalence value of 3.40 (1.13 – 10.22), 2.01 (1.14 – 3.56), 2.39 (1.36 – 4.20), and 2.07 (1.12 – 3.83). Conclusion: Factors of young age <40 years, male sex, unmarried, and unemployed are risk factors for the occurrence of agitation in schizophrenic patients at Dr. Amino Gondohutomo Semarang Regional Psychiatric Hospital.